Schwann Cell Development and Pathology - Sango, Kazunori; Yamauchi, Junji; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2014)
This book presents recent topics on the development, differentiation, and myelination of Schwann cells, as well as pathological mechanisms and therapeutic approaches for peripheral neuropathies, such as Charcot–Marie–Tooth diseases, amyloid polyneuropathy, immune-mediated neuropathy, and diabetic neuropathy. The rapid progress of molecular biological techniques in the last decades, especially for RNA techniques and gene modification technologies, have allowed us to investigate the pathobiology of Schwann cells in vivo and in vitro. Studies combining recent stem cell biology with recent biotechnology, which is now closely linked to physicochemical fields, further explain how Schwann cell lineages develop, a process that has long been thought to be very complicated in vivo. The findings contribute to the elucidation of fundamental mechanisms during development and under pathological conditions. We now know that these are closely tied to each other. This book also introduces unique coculture systems to reproduce the neuron–Schwann cell interplay during development, degeneration, and regeneration. Up-to-date research topics with high-quality immunofluorescence and electron micrographs introduced by young and energetic contributors are sure to arouse the readers' interest in Schwann cell biology. Discussion from the viewpoint of basic and clinical neuroscience makes the book educational for researchers, medical students, and young clinicians.
Foreword -- Preface -- 1 Introduction (Kazunori Sango and Junji Yamauchi) -- 2 Recent insights into molecular mechanisms that control growth factor receptor-mediated Schwann cell morphological changes during development (Yuki Miyamoto and Junji Yamauchi) -- 3 Membrane Skeleton in Schmidt-Lanterman Incisure in Schwann cells of Peripheral Nervous System (Nobuo Terada, Yurika Saitoh, Nobuhiko Ohno, and Shinichi Ohno) -- 4 Schwann cell-axon interactions: the molecular and metabolic link between Schwann cells and axons (Nobuhiko Ohno, Takashi Sakoh, Yurika Saitoh, Nobuo Terada, and Shinichi Ohno) -- 5 Schwann cell-dependent regulation of peripheral nerve injury and repair (Keiichiro Susuki ) -- 6 Charcot-Marie-Tooth disease (Toru Ogata) -- 7 Expression of the transthyretin gene in Schwann cells, and familial amyloidotic polyneuropathy-mediated neurodegeneration (Tatsufumi Murakami and Yoshihide Sunada) -- 8 Node of Ranvier disruption: a key pathophysiology in immune-mediated neuropathies (Keiichiro Susuki ) -- 9 Pathogenesis of diabetic neuropathy from the viewpoint of Schwann cell abnormalities (Koichi Kato, Eva L. Feldman, and Jiro Nakamura) -- 10 Spontaneously immortalized adult rodent Schwann cells as valuable tools for the study of peripheral nerve degeneration and regeneration (Kazunori Sango, Masami Tsukamoto, Kazunori Utsunomiya, and Kazuhiko Watabe) -- BM Index.
Keywords: Neurosciences; Neurology .; Neurobiology; Neurosciences; Neurology; Neurobiology